EVALUATING THE FLEXURAL STRENGTH OF CORRODED REINFORCED CONCRETE BEAMS - Ibim Green; Kelechi Ugoji (International Journal of Innovations in Engineering Research and Technology, 2023)
Corrosion of reinforcing steel is one of the most deterioration factors that influence reinforced concrete structures. Quantifying the effect of corrosion before structural failure is significant for a cheaper and more efficient repair. In this paper, a simple model was used to predict the residual flexural strength of RC beams with varying degrees of reinforcement corrosion based on experimental results. The Model was developed from analysing several beam specimens available in literature, which have been damaged by accelerated corrosion. The validity of this study was compared with separate set of published data. The new proposed model in this study was able to successfully predict the residual flexural strength of corroded reinforced concrete beams. It is recommended to study in future work the applicability of this model to full-scale RC beams that underwent natural corrosion or failed in flexure by concrete crushing.